1995
DOI: 10.1007/bf01314641
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol, sexual behaviour and drug use in women with cervical human papillomavirus infection

Abstract: The results of this study indicate that smoking, alcohol and drug abuse are risk markers, but not causal factors, for CHPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Conversely, two studies found no relationship between alcohol intake and HPV endpoints. A cross-sectional analysis of women seeking contraceptive advice in three Swedish clinics reported that recent use of alcohol was not associated with cervical HPV infection after adjustment for sexual/behavioral factors (25). In a separate study among high-risk HPV-positive women, alcohol intake was not associated with risk of high-grade squamous intraepithelial lesions (26).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, two studies found no relationship between alcohol intake and HPV endpoints. A cross-sectional analysis of women seeking contraceptive advice in three Swedish clinics reported that recent use of alcohol was not associated with cervical HPV infection after adjustment for sexual/behavioral factors (25). In a separate study among high-risk HPV-positive women, alcohol intake was not associated with risk of high-grade squamous intraepithelial lesions (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature data regarding the potential relationship between alcohol consumption and HPV infection are conflicting. A previous study showed that there is a positive relationship between alcohol and HPV infection [39], while a recent one showed no relationship [40]. On the contrary, HPV infection declined with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Factors which influence risk for cervical cancer such as infection with HPV, smoking, multi parity, oral contraceptives usage, early onset of sexual intercourse and multiple sexual partners may very well be confounders in the current study. [44][45][46][47][48] Incorporating these socio-demographic factors will thereby also justify an increase in the sample size but overcoming these limitations in future studies may greatly improve the results, potentially providing more clarity in identifying SNP-malignancy associations.…”
Section: Discussionmentioning
confidence: 99%